Player tracking technology and data for injury prevention in the National Football League - Ghasem, W.; Valenzuela, J.; Saxon, L. A. (Current Sports Medicine Reports, 2021)
The recent partnership of NFL`s Next Gen Stats with Amazon Web Services has created a buzz among media and fans, yet the full scope and utility of digital biosensors has yet to be determined. We review current uses of Global Positioning System technology and digital biosensors in the NFL and discuss the future role of this technology in injury prevention. A complete literature review was conducted, along with review of the NFL web site and news outlet articles, to obtain a comprehensive assessment of all prior and current uses of biosensor technology in the NFL. Limited data exist on successful injury prevention and return to play, and utilization of this emerging technology has mostly been for fan experience. While ethical and legal challenges exist, the integration of digital biosensor and GPS technology in the NFL has enormous potential and is an invaluable tool in the comprehensive assessment of player health.